Characterization of beet-pulp fiber reinforced potato starch biopolymer composites for building applications - Karaky, Hamzé; Maalouf, Chadi; Bliard, Christophe; Gacoin, Alexandre; Lachi, Mohammed; El Wakil, Nadim; Polidori, Guillaume (Construction and Building Materials, 2019)
This work deals with the making of a new renewable green material for building insulation from sugar beet pulp and potato starch. The material is both lightweight and ecofriendly. The influence of starch/extruded sugar beet pulp mass ratio (S/EBP) is studied. Four mass ratios are considered, 10, 20, 30 and 40% (relative to the starch). Samples are characterized in terms of absolute and bulk density, sound absorption coefficient, compressive and flexural strength, as well as and hygrothermal properties (the moisture buffering value and thermal conductivity). The sound absorption coefficient shows that this material is a good sound absorber, especially in medium and high frequencies. The sound absorption capacity depends on the fiber content and the humidity content. The best values are between 0.6 and 0.8. The compressive strength increases linearly with the S/EBP weight ratio to reach 0.52 MPa and the compressive strain is 30%. The elasticity modulus and the Poisson’s ratios were also studied. The transversal and vertical strain were measured using ARAMIS optical system. The moisture buffering value was measured according to Nordtest Protocol. The recorded moisture buffering value was between 2.6 and 2.8 g/(%RH.m2) and shows that the sugar beet pulp-starch composite is an excellent hygric regulator. The thermal conductivity is to around 0.070 W/(m·K). The results obtained shows that increasing starch amount tends to decrease composite porosity but increases thermal conductivity and mechanical properties. Depending on the starch content, beet pulp composites have a good thermal and acoustical performance and can be used as building materials.
Keywords: Bio-sourced composite; Building insulation; Hygrothermal properties; Mechanical properties; Moisture buffering value; Porosity; Potato starch; Sound absorption; Sugar beet pulp